Dynamics of Vegetation of High Mountain Areas of the Northern Tian Shan under Different Protection and Economic Use Regimes - IMANKULOVA, Sofia K.; SHALABAYEV, Karatay I.; MUSSAEV, Kuandyk L.; ISSABEKOV, Beibit M.; AMANBEKOVA, Dinara M. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
The territory of Kazakhstan is located in the center of the continent of Eurasia and has a considerable area of 272.5 million ha. This geographical position predetermines a great variety of species of flora and fauna. This research presents the results of studies of the current state of vegetation of the high mountain valley Kok Zhailau, located in the central part of the Ile (Zailiysky) Alatau ridge (Northern Tian Shan), in different modes of its economic use and protection. In the process of the field survey of the territory, classical methods of route floristic and geo-botanical studies were used. The spatial structure and current state of vegetation was studied using methods of detailed path research. A brief description of distribution of the main types of vegetation in high altitude zones was provided. Particular attention is paid to the analysis of coniferous forests from relict spruce Schrenka or Tian Shan (Picea schrenkiana Fisch & C.A. Mey). Recommendations were given on the protection of vegetation and the conservation of biodiversity in the face of an increasing anthropogenic impact, in connection with the proximity of the territory to the metropolis of Almaty. The survey demonstrated that, in general, the vegetation cover in the Kok Zhailau valley was to some extent transformed, and in its natural (background) state it was preserved only in hard-to-reach areas, mainly in the upper part of the mountains (steep slopes of the Kumbel ridge, river valleys, etc.).